FOCUS GROUP DISCUSSION AS COMMUNICATIVE ACTIVITY IN ENCHANCING STUDENTS’ SPEAKING SKILL AT SMAN 5 BARRU - Nirma; Sujariati; Ariana (FKIP Unismuh Makassar, 2024)
This article identifies a problem with students' ability to speak in public, especially in the use of English. Therefore, the researcher provides a method as a goal to improve the speaking ability of students specifically in the use of English. therefore, researching a method in this case Focus Group Discussion as a Communicative Activity in Improving Students' Speaking Skills at SMAN 5 Barru. From this article, speaking improvement can be contained from two things, namely looking at the conversation and how much vocabulary is used as a benchmark for improving students' speaking. The method used by the researcher is a quantitative research model with three stages, namely pre-test, treatment and post-test to obtain results. From these results, after being given the Focus Group Discussion method, there was an increase from before the method was given. Therefore, the Focus Group Discussion method is good to use in the learning process to improve students' speaking skills, especially in learning English.